2021
DOI: 10.2147/dmso.s311462
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Work-Related Factors Associated with Work Ability and Work Participation for People with Obesity: A Prospective Observational Study After Vocational Rehabilitation

Abstract: Purpose We aimed to investigate which changes in the explanatory factors that were associated with positive change in the work ability score (WAS) and degree of work participation (DWP) for participants in a new 1-year vocational rehabilitation (VR) program for people on or at risk of sick leave due to obesity or obesity-related problems. Patients and Methods This prospective observational study included 95 participants with a body mass index (BMI) above 30 kg/m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Higher self-perceived health, more comorbidities and higher pain intensity at the beginning of rehabilitation were all associated with work ability one year later, underscoring their significance for self-perceived work ability. These findings align with existing research, reporting associations between self-perceived health and work ability [7,50], and pain and work ability [51], and that having rheumatic and musculoskeletal diseases concurrent with comorbidities is associated with poorer health, higher ratings of pain, psychological distress and work disruptions [22]. People who experience impaired health consider themselves not capable of work, and exhibit a low motivation to participate in the labor market [52].…”
Section: Discussionsupporting
confidence: 83%
“…Higher self-perceived health, more comorbidities and higher pain intensity at the beginning of rehabilitation were all associated with work ability one year later, underscoring their significance for self-perceived work ability. These findings align with existing research, reporting associations between self-perceived health and work ability [7,50], and pain and work ability [51], and that having rheumatic and musculoskeletal diseases concurrent with comorbidities is associated with poorer health, higher ratings of pain, psychological distress and work disruptions [22]. People who experience impaired health consider themselves not capable of work, and exhibit a low motivation to participate in the labor market [52].…”
Section: Discussionsupporting
confidence: 83%
“…However, changes in work participation can also depend on factors not directly affected by health or lifestyle changes, such as relations with managers and co-workers and other workplace factors. Workplace modifications can contribute to increased work ability as well as prevent sick leave (Franche & Krause, 2002 ; Kristman et al, 2020 ; Linge et al, 2021a , 2021b ; Schultz et al, 2007 ; Young et al, 2005 ), and job satisfaction has been shown to be an important factor for well-being at work (Ekberg & Ståhl, 2020 ; Figueredo et al, 2020 ; Hees et al, 2012 ; Linge et al, 2021b ; De Vries et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, work focus has not been a part of lifestyle interventions for persons with obesity in Norway, although there is an increasing awareness of the problem of reduced work ability for this group (Linge et al, 2021a , 2021b ). In order to meet the challenges that persons living with obesity face regarding their working life, a newly developed work intervention was introduced as an additional element to a lifestyle intervention programme for persons with morbid obesity.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 Further, publications indicate also that weight reduction may improve work ability and work participation. 15–17 To manage health and functional capacity problems and adjust contextual factors, people in Norway can receive help through governmental-funded vocational rehabilitation (VR). 18 , 19 VR aims not to cure illness but to promote work participation despite sickness and health complaints.…”
Section: Introductionmentioning
confidence: 99%
“… 21 Previous research has indicated that people attending VR programmes may enhance work ability and reduce sick leave. 15 , 22 , 23 …”
Section: Introductionmentioning
confidence: 99%